Reverse Sweep Opportunity in Facing Bad Pressure Early Marriage Based on Society 5.0 and Industry 4.0 - Bagas, Bagas Arri Atmaja; Ramadani, Febiola Djangkaru (SERUNAI, 2024)
This research entitled "Reverse Sweep Opportunity In Facing The Bad Pressure Of Early Marriage In Indonesia" aims to address the problem of early marriage that continues to increase in Indonesia, which is often triggered by economic and cultural factors. Unlike previous studies that tend to focus on statistical data analysis, this study carries the concept of "Reverse Sweep" which is oriented towards mental strengthening and social support. The researchers' motivation stems from concerns about the negative impacts of early marriage, such as mental health and lost life opportunities for the younger generation.The methodology used is a qualitative descriptive approach, with data collection through interviews, observations, and documentation at junior high schools in Tambakrejo Village, Bojonegoro Regency. The results of the study show that the application of the concept of Roots and Support in the counseling forum "CurhatYuk!" has succeeded in helping more than 1,000 clients in overcoming problems related to early marriage and mental health.The policy implications of this study suggest the need for an integrated, community-based intervention program, which not only educates about the risks of early marriage, but also provides emotional and economic support to the bride-to-be and her family. This research is expected to be a reference for efforts to create a Golden Indonesia through improving the quality of life and mental health of the community.